Effects of direct lightning strike on vertical axis wind turbine blade materials - Siti Hawa Noor Aidy, 1993-, author; Zuraimy Adzis supervisor; Fakulti Kejuruteraan Elektrik (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2016